Exploring the Experience of Loneliness in the Older Single Women in Tehran City, Iran - Hajar Karami -Agh Ghaleh; Tahereh Dehdari; Ava Sadat Hosseini (Sālmand)
Objectives Although loneliness can occur in any life stage, its is higher among older adults. The present study aimed to explore the experience of loneliness in single older women in Tehran, Iran. Methods & Materials This qualitative study was conducted from 2020 to 2021. Sampling was performed using the snowball method. The participants were 23 older women aged 60-70 years remained permanently single unmarried, and had lived alone for at least one year, in Tehran, Iran. Data were collected using in-depth semi-structured individual interviews and the collected data were analyzed using the conventional content analysis. Results The mean age of women was 62.1 years. After coding and analyzing the data, three main themes were extracted as the participants' experiences of loneliness: Coping with loneliness (with two categories of adaptive and maladaptive coping strategies), consequences of living alone (with two categories of perceived benefits and perceived disadvantages) and mediators of coping with loneliness (with three categories of social factors, physiological factors, and socio-economic factors) were recognized. Conclusion The experiences of older women remained unmarried and are living alone, explored in this study, can significantly clarify their needs. Necessary planning is required to address their needs and challenges.